Sudden cardiac death and valvular pathology - Rosa H. A. M. Henriques de Gouveia; Francisco M. A. Corte Real Gonçalves (Forensic Sciences Research, 2019)
Sudden death due to valvular heart disease is reported to range from 1% to 5% in native valves and around 0.2%–0.9%/year in prosthesis. The nature of the diseases is varied, from heritable, congenital to acquired. It may affect both genders in multiple age groups. The authors show and comment examples of the major nosologic aetiologies underlying unexpected exitus letalis of valvular nature.